The Dialogical Tradition of Iranian Modernity: Monazereh, Simultaneity, and the Making of Modern Iran. Issue 3 (3rd May 2016) - Rezaeiyazdi, Hamid
Abstract : Iranian modernity has chiefly been examined in the context of a dialectical antagonism between "traditionalists" and "modernists"—main categories comprised of related sub-headings such as "Islamist" versus "secular, " "reactionary" versus "revolutionary, " and "regressive" versus "progressive." Following this approach, Iranian adaptations of modernity have often been (de)historicized as a theater of national "awakening" resulting from the toils of secular intellectuals in overcoming the obstinate resistance of traditional reactionaries, a confrontation between two purportedly well-defined and mutually exclusive camps. Such reductionist dialectics has generally overwritten the dialogic narrative of Iranian modernity, a conflicted dialogue misrepresented as a conflicting dialectic. It has also silenced an important feature of Iranian modernity: the universally acknowledged premise of the simultaneity and commensurability of tradition with modernity. The monazereh (disputation or debate) is the account of the interaction between rival discourses that engaged in opposing, informing, and appropriating each other in the process of adapting modernity. Narrativizing the history of Iranian modernity as the conflict between mutually exclusive binaries overlooks its hyphenated, liminal 1 identity—a narrative of adaptation rather than wholesale adoption, of heterogeneity rather than homogeneity, of dialogues rather than dialectics. The monazereh is the account of modern Iranian histories.